The Effect of Bloodletting Therapy on Lipid Metabolism and Glucose Control in Type 2 Diabetes: A Case Report - Tserentogtokh Baasantogtokh; Seesregdorj Surenjid; Sainbileg Sonomtseren; Tsolmon Unurjargal; Wei-Ti Chen; Nominerdene Ulambayar; Enkhtuya Vankhuu (Trends in Immunotherapy, 2026)
Type 2 diabetes mellitus (T2DM) is a pervasive chronic metabolic disorder characterized by insulin resistance and hyperglycemia. While conventional treatments exist, there is groqing interest in complementary and alternative therapies, particularyl for patients with poorly controlled disease. . Among these, bloodletting therapy of Traditional Mongolian medicine (TMM) has historical roots, yet it lacks robust scientific evaluation. This case report presents a 42-year-old male with uncontrolled T2DM and concomitant dyslipidemia, who demonstrated poor adherence to standard glucose-lowering medications. The therapeutic intervention involved a traditional Mongolian medicine protocol, commencing with a 5-day preparatpry regimen of an herbal blood-thinning decoction. This was followed by th bloodletting procedure itself, with no conventional anti-diabetic medications administered during the entire intervention period. This outcomes observed over 90-day follow-up were notably substantial. The patient’s metabolic parameters demonstrated framatic improvements: fasting glucose decreased from 13.89 to 5.77 mmol/L, and glycated hemoglobin (HbA1c) fell from 7.31% to 6.05%. Significant enhancements were also recorded in lipid metabolism, with cholesterol and triglyceride levels dropping from 6.1 to 4.65 mmol/L and from 8.35 to 2.43 mmol/L), respectively. Furthermore, the patient exhibited considerable reductions in body mass index (from 35.7 to 29.5 kg/m²), and blood pressure (140/90 to 130/85 mmHg), no serious adverse events reported. In conclution, the combination of traditional Mongolian bloodletting and an herbal decoction was associated with clinically meaningful improvements in glycemic control, lipid profile, and overall metabolic balance in this refractory uncontrolled T2DM case. These promising findings suggest potential immunometabolic benefits; however, rigorous controlled studies are imperative to definitively confirm its efficacy, safety, and the underlying mechanisms of action.